Cross-chest liposuction plus gland resection through single minimal incision for management of grade I/II gynecomastia - Saber M. Abdelmaksoud; Ahmed Omran; Khaled Maher Muhammad Elagamy; Mahmoud Abdelhamid Elhendawy; Barakat Abdelreheem Mahmoud (BMC Surgery)
Abstract Background and aim In modern gynecomastia surgery, minimally invasive access and fast recovery have been advocated as essential management concepts. The present study aimed to describe the surgical details and clinical outcome of a minimally invasive approach combining cross-chest liposuction and minimal incision gland resection for management of grade I/II gynecomastia. Methods The present retrospective study included 30 patients with grade I/II gynecomastia. Surgery was conducted under general anesthesia with the patient placed in the supine position and arms abducted 90○ at the chest. The whole surgical procedure was achieved through a minimal 1-cm stab incision made at the inferolateral areolar border. The incision was used for injection of tumescent solution, liposuction and gland excision. The operative outcome was assessed by both patients and independent surgeons. Evaluated aesthetic aspects included breast symmetry, nipple and areola shape, projection of the nipple-areolar complex (NAC), contour regularity, and overall appearance. Results Postoperative complications included hematoma (3.3%) and hypopigmented scar (6.7%). Patient-reported scores for breast symmetry, nipple and areola shape, projection of the nipple-areolar complex, contour regularity and overall appearance were 4.2 ± 0.4, 4.3 ± 0.5, 4.3 ± 0.4, 4.1 ± 0.3 and 4.4 ± 0.5 respectively while surgeon-reported scores for breast symmetry, nipple and areola shape, projection of the NAC, contour regularity and overall appearance were 4.5 ± 0.5, 4.4 ± 0.5, 4.4 ± 0.5, 4.2 ± 0.4 and 4.1 ± 0.3 respectively. Conclusions The combination of cross-chest liposuction and gland excision through a single minimal incision at the inferolateral areolar border provides good and satisfactory aesthetic outcomes for patients with grade I/II gynecomastia.